The temperature and pH dependence of conformational transitions of the chromatin subunit. - Gordon, V C (1979)
Hydrodynamic, spectroscopic, and chemical crosslinking studies on monomer chromatin subnits are reported as a function of ionic strength, pH, and temperature. In earlier studies, two salt-dependent conformational transitions were described (Gordon et al., Proceedings of the National Academy of Science, 75, 660, 1978). Transition one occurred between 0.7 and 2.0 mM ionic strength and transition two occurred between 5.0 and 11.0 mM ionic strength. Crosslinking at 11 mM ionic strength with formaldehyde suppressed both transitions. In this communication we report that the second transition was characterized by changes in the circular dichroism spectra in the 260--320 nm region as well as by changes in the hydrodynamic properties. As the ionic strength was increased from 5.0 to 11.0 mM, [theta]282 decreased from 2000 TO 1500 DEG CM2/DMOLE AND [THETA]295 decreased from 0 to -400 deg cm2/dmole. Both transitions occurred in the pH range from pH 6.0 to 9.2. At pH 5.0, the two ionic strength-dependent transitions were no longer observed and the characteristic changes in the circular dichroism spectra were suppressed. The spectra of the monomer subunits at pH 5.0 showed only small changes with ionic strength and resembled the spectra of the subunits at 11 mM ionic strength above pH 6.0. In order to characterize the transitions in thermodynamic terms an ionic strength near the midpoint of each transition was selected. Then, changes in s20,w and D20,w were measured as a function of temperature. These data allow an estimation to be made of the enthalpies and entropies of the transitions.